EFEKTIVITAS MODEL PEMBELAJARAN DALAM UPAYA MENINGKATKAN KEMAMPUAN MEMBACA AWAL BAGI SISWA SEKOLAH DASAR - Salamah Salamah (MAJALAH ILMIAH PEMBELAJARAN, 2008)
This action research was aimed at finding out of which instructionalmodel can improve the effectiveness of the teaching of early reading. Theaction research was conducted through several steps preliminary action,the formulation of instructional model, discussions to share researchconcepts, the implementation of actions, monitoring, reflection, andrevision.Research findings showed that the effectiveness and efficiency ofthe teaching improved because of (a) the teaching method which usedsound and media games, (b) stimulating students to think analytically andsyntecally, (c) classical teaching, (d) individual learning, (e) learningguided by care instructional material, and (f) grouping the material, (g)spelling, sentence variation.